A case study of the characteristics of municipal solid waste in Asturias (Spain): influence of season and source. Issue 4 (April 2013) - Castrillón, Leonor; Fernández-Nava, Yolanda; González, Angela; Marañón, E
In the present research study, the weight composition, physical–chemical composition and net calorific values of unsorted municipal solid waste (MSW) generated by a population of around 1, 080, 000 inhabitants in a region of northern Spain were determined. The unsorted MSW was composed of 38.1% organic fraction and 42.3% combustible fraction, with paper/cardboard constituting the most important part of the latter fraction (20.6%). The high content of textiles (10.9%) is worth noting, being practically equal to the content in plastics. The unsorted fractions present an average moisture content of 28.5% and an ash content of 29.4% (dry basis). The average lower heating value (LHV) is 10, 744 kJ kg -1 . Likewise, variations in regard to the season of the year and the source of the waste were taken into consideration. A new correlation is proposed for estimating the LHV as a function of the physical composition of the waste.